Rationally Engineered Tandem Facial Amphiphiles for Improved Membrane Protein Stabilization Efficacy. (21st September 2018) - Das, Manabendra; Du, Yang; Mortensen, Jonas S.; Hariharan, Parameswaran; Lee, Hyun Sung; Byrne, Bernadette; Loland, Claus J.; Guan, Lan; Kobilka, Brian K.; Chae, Pil Seok
Abstract: A new family of tandem facial glucosides/maltosides (TFGs/TFMs) for membrane protein manipulation was prepared. The best detergent varied depending on the hydrophobic thickness of the target protein, but ether‐based TFMs (TFM‐C0E, TFM‐C3E, and TFM‐C5E) were notable for their ability to confer higher membrane protein stability than the previously developed amide‐based TFA‐1 (P. S. Chae, K. Gotfryd, J. Pacyna, L. J. W. Miercke, S. G. F. Rasmussen, R. A. Robbins, R. R. Rana, C. J. Loland, B. Kobilka, R. Stroud, B. Byrne, U. Gether, S. H. Gellman, J. Am. Chem. Soc. 2010, 132, 16750–16752 ). Thus, this study not only introduces novel agents with the potential to be used in membrane protein research but also highlights the importance of both the hydrophobic length and linker functionality of the detergent in stabilizing membrane proteins. Abstract : Situation stabilized : Tandem facial glucosides/maltosides (TFGs/TFMs) are prepared for membrane protein manipulation. The best detergent depends on the hydrophobic thickness of the target protein, but ether‐based TFMs confer higher membrane protein stability than a previously developed amide‐based amphiphile. This study highlights the importance of the hydrophobic length and linker functionality of the detergent for stabilization of membrane proteins.